ANALISIS KEMAMPUAN MAHASISWA PENDIDIKAN BAHASA INGGRIS SEMESTER VI UNIVERSITAS PASIR PENGARAIAN DALAM MENULIS CRITICAL ESSAY - Rasyidah, Ummi; Antoni, Rivi (Edu Research, 2014)
Writing critical essay can be simple and complicated in the same time. Critical essay is more than presenting and summarizing. It is an analitycal work.Dealing with statement above, a descriptive research is conducted in University of Pasir Pengaraian. The aims of this research are (1) to find out students’ ability in writing critical essay and (2) to explore factors affecting students’ writing critical essay skill. After analyzing the data quantitatively and qualitatively, it is found that the students’ ability in writing critical essay is 57,63 while factors affecting their writing skill are motivation, types, length and content of texts.